Design of an Optical Emitting System for Scannerless Imaging LIDAR Based on ZEMAX - Muhmmad Rizwan Anjum; Wang Xiaowei; Khanzada T. J. S.; M. A. Shaheen (Institute of Advanced Engineering and Science, 2014)
Optical emitting system is an essential part of scannerless imaging LIDAR. It plays an important role in decreasing the divergence angle and homogenizing the beam spot which have an immense influence on the light signal back from the target. This research work proposes the design of the system using ZEMAX model also determine the includes shaping and zooming features of design model. In the shaping system feature we used two cylindrical lenses whose accurate positions have been solved by using the theories of matrix optics and Gauss optics. The cam curve of a three-group zoom system with (2x-7x) zoom ratios has been drawn. The simulation results verify the availability that the beam from the laser diode meets the requirements after optical emission from system.